1989
DOI: 10.2307/3282765
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Lethality of Bacillus thuringiensis kurstaki Toxin for Eggs and Larvae of Trichostrongylus colubriformis (Nematoda)

Abstract: A toxin from Bacillus thuringiensis kurstaki was lethal to eggs and first- and second-stage larvae of the ruminant nematode Trichostrongylus colubriformis. Sheathed and exsheathed third-stage larvae were also killed by the toxin. However, susceptibility of the ova to the toxin decreased after several hours of development. Heating at 65 C for 1 hr or freezing at 0 C for 3 mo did not affect stability of the toxin. Ovicidal activity of the toxin was not altered by treatment with 13 microbial or mammalian enzymes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…thuringiensis kurstaki and another parasporal crystal‐forming bacterium, Bacillus sphaericus , showed that some strains had significant activity on the eggs and larvae of the parasitic nematode Trichostrongylus colubriformis (Bottjer et al , 1986; Bowen et al , 1986a, b; Bowen & Tinelli, 1987; Meadows et al , 1989). The toxicities of these strains were inhibited by antibiotics and did not correspond to the sporulation phase of the bacteria, nor to their resistance to alkaline pH and heat, demonstrating that the pathogenic factors were not the parasporal crystal (Bottjer et al , 1986; Bowen et al , 1986a, b; Bowen & Tinelli, 1987; Meadows et al , 1989). Subsequently, an unknown Bt isolate was also reported to have toxicity to root‐lesion nematodes (Bradfish et al , 1991).…”
Section: Nematophagous Bacteria and Their Modes Of Action Against Nemmentioning
confidence: 99%
“…thuringiensis kurstaki and another parasporal crystal‐forming bacterium, Bacillus sphaericus , showed that some strains had significant activity on the eggs and larvae of the parasitic nematode Trichostrongylus colubriformis (Bottjer et al , 1986; Bowen et al , 1986a, b; Bowen & Tinelli, 1987; Meadows et al , 1989). The toxicities of these strains were inhibited by antibiotics and did not correspond to the sporulation phase of the bacteria, nor to their resistance to alkaline pH and heat, demonstrating that the pathogenic factors were not the parasporal crystal (Bottjer et al , 1986; Bowen et al , 1986a, b; Bowen & Tinelli, 1987; Meadows et al , 1989). Subsequently, an unknown Bt isolate was also reported to have toxicity to root‐lesion nematodes (Bradfish et al , 1991).…”
Section: Nematophagous Bacteria and Their Modes Of Action Against Nemmentioning
confidence: 99%
“…Pasteuria penetrans can control the spread of root knot nematodes in soil, but this bacterium, which is an obligate parasite, is difficult to grow under laboratory conditions and does not survive well in soil (21). Recently, research has focused on other bacteria for control of parasitic nematodes (1,15,16), with the objective of proposing strategies for inhibition of egg hatch (10,24), degradation of the hatching factor (15), or production of metabolites toxic to juvenile nematodes (14).…”
Section: The Potato Cyst Nematode Globodera Rostochiensis Is An Impormentioning
confidence: 99%
“…Over the last decades, research on root-knot nematode control was focused on proposing strategies for inhibition of egg hatch (Westcott and Kluepfel, 1993), degradation of hatching factor (Oostendrop and Sikora, 1989) or production of metabolites (Meadows et al, 1989). In particular, the search for nematode-antagonistic compounds from culture filtrates of fungi has greatly intensified in recent years because of the large number of toxins and potential new drugs among fungal metabolites.…”
Section: Introductionmentioning
confidence: 99%